Pay Secrecy: Who Is For And Against It? - Schuster, Jay R.; Colletti, Jerome A. (Academy of Management Journal, 1973)
Researchers have argued at length about the motivational role of pay secrecy. This research investigates the characteristics of individuals who want pay kept secret and those who do not. Findings indicate that better performers want pay kept secret slightly more than poor performers.